Station-network cooperative planning method of urban integrated energy system based on energy flow model - Fu, Xin; Yu, Shunjiang; He, Qibo; Wang, Long; Niu, Chengeng; Yang, Li (Frontiers in Energy Research, 2024)
Coordinated siting and sizing for energy stations and supply networks in urban integrated energy system (UIES) is significant for economic improvement and carbon emissions reduction. A station-network cooperative planning method of UIES based on energy flow model is proposed. First, an operation model of heat network based on energy flow theory is proposed, which solves the problem that the temperature mixing equation in the traditional operation model cannot be applied to heat network planning. On this basis, a bi-level model for station-network cooperative planning of UIES is constructed, in which the upper level optimizes the siting and sizing of the energy station and the topology of the supply network, and the lower level optimizes the operation of the UIES and feeds back the operation cost of the UIES to the upper level. Finally, a solution method of cooperative planning based on the Karush-Kuhn-Tucher condition is proposed, to transform the bi-level nonlinear optimization model into a single-level linear optimization model for efficient solution. Case studies on the 55-node and 77-road urban topology show that the proposed method can perform an effective planning on energy supply network topology and rationally configure the capacity of various devices in the energy station.